Is it Possible to See a Human Facial Expression during Rapid Eye Movements? - V A Barabanschikov; I Yu Zherdev (Peoples' Friendship University of Russia (RUDN University), 2014)
The identification accuracy of intense basic facial expressions during the saccadic eye movements is studied. An original hardware-software apparatus based on high frequency video eyetracker was used which makes it possible to change visual stimulus twice during a saccade. A reliable identification at a frequency of 0,61 is observed. The identification frequency is related both to the expression modality and alternative response. No relation to egocentric stimulus position is observed.